Knowledge and practice about contraception among married women in reproductive age group in a rural area of Tirunelveli district, Tamil Nadu, India: a cross-sectional study - A., Praveena Daya; G., Prema Priya; G., Karthikeyan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Unmet need for contraception is still high in developing countries because of various reasons and poses a great challenge to the success of family welfare programme Assessing the knowledge and filling the gap is essential for successful functioning of the programme and for reducing the unmet need. Methods: A cross-sectional study was conducted to assess the knowledge and practices on contraception among 100 married women in reproductive age group (15-49 years) residing in a Rural Health centre area of Tirunelveli district, Tamil Nadu, South India. Results: Among the 100 participants, common known methods of contraception were IUD (56%), permanent sterilization (38%), Pills (21%) and Condoms (14%). Out of 100 participants, only 38 were using contraception. Among the 62 who are not using any method of contraception, 30 are willing to practice contraception after motivation and among them 27 prefer to use temporary methods. Fear of side effects was most common reason stated for not using contraception. Conclusions: Knowledge and practice related to contraception among the participants were observed to be less. Health education campaigns emphasizing the need of family planning and about the services available in the government health facilities has to be organized regularly.